DO EMISSOR AO RECEPTOR: os múltiplos caminhos da mensagem publicitária na campanha nacional de vacinação do idoso contra a gripe - Hossoé, Hayleno Santos (2007)
This research has as main objective to evaluate the reception and the adequacy of the advertising of the Campanha Nacional de Vacinação do Idoso Contra a Gripe of the district of São Luís do Maranhão in the year of 2006, considering its goals and its proposal of communication. Therefore, an ex-post evaluation of the implementation of the program of vaccination, classified as process of evaluation, was carried through aiming to relating the adequacy of the advertising campaign to the objectives and goals of this program, using an exploratory and qualitative approach. Documentary research, direct observation and focal group were used as techniques for data collection. Six participants of third age focal groups were carried through after the propagation of the 2006 campaign, in order to apprehend the generated effect of the communicative process in its target public. The accomplishment of each focal group was segmented in two stages. The first one was guided by a halfstructuralized script in order to motivate the quarrel of the participants on the campaign without showing its parts. The second stage was based on the exposition of the advertising parts of the campaign in order to stimulate the memory of the participants and to make possible the apprehension of the reception of the message without the interference of any imperfection in the distribution of the communication. The data collected through direct observation and the focal group participants` comments made possible the constitution of a research corpus on which an Analysis of Content was carried through by techniques of Thematic Analysis, with the purpose to compose an index which makes possible to extract, to classify and to regroup the speech of the subjects, in order to allow the identification of the elements that constituted the reception of the advertising campaign from the point of view of the integrants of its target public. Through the Thematic Analysis and the evaluation of the implementation process, it was possible to conclude that imperfections occurred in the process of distribution of parts of the advertising campaign, but they did not harm the positive results and reached number of vaccine covering in the year of 2006.